Evaluation of Transformational Leadership of Principals in Improving Teacher Performance at SDN 1 Bojong Timur Purwakarta Regency - Rohmat Umara; Irma Nurmilah; Dinny Mardiana; Suharyanto H Soro (Civiliza Publishing, Indonesia., 2025)
Teachers are an important factor in the success of the learning process; therefore, teacher performance directly influences the quality of education. The principal's leadership also plays an important role in enhancing teacher motivation and performance. While previous studies have indicated that transformational school leadership has a positive impact on teacher performance, it remains unclear how the evaluation process within transformational leadership specifically improves performance. This study aims to analyze the controlling stage, based on Henry Fayol’s theory, of transformational school leadership in an effort to enhance teacher performance. This research employs a qualitative method with a case study approach. Data were collected through observation, in-depth interviews, and documentation studies. Samples were selected via purposive sampling, involving the school principal as a manager and teachers meeting specific criteria. Overall, the results indicate that the transformational leadership practices of the principal align with Henry Fayol’s POCCC theory, particularly in the controlling stage. In practice, the principal exercises control through supervision and collective reflection with teachers, which is documented in a supervision book. This book contains records of planned activities adjusted to the school’s vision and mission. The study concludes that transformational leadership at SDN 1 Bojong Timur, Purwakarta Regency, has proven successful in increasing teachers' morale, motivation, and responsibility, thereby contributing positively to the improvement of teacher performance.